Perubahan Tutupan Hutan Mangrove Di Pesisir Kabupaten Lampung Timur - Yuliasamaya Yuliasamaya; Arief Darmawan; Rudi Hilmanto (Jurnal Sylva Lestari, 2014)
The purposes of this study were: (1)to describe the change of mangrove forest cover along the coast of East Lampung Regency using Landsat data for 1973, 1983, 1994, 2004, and 2013; (2)to determine triggering factors that occur in the coast of East Lampung Regency during the years 1973-2013 related to the mangrove forest change. The methods used in the study are spatial analysis and qualitative descriptive method. The study was conducted along the coast of East Lampung Regency over period of October 2013-March 2014. The result shows that: in 1973-1983 increased by 2,541.22 ha, in 1983-1994 decreased by 4,903.54 ha, in 1994-2004 decreased by 6,377.11 ha, in 2004-2013 decreased by 3,059.23 ha. The related factors that occur in there were changes in the status management area is happening in Way Kambas National Park (TNWK), there were people migration into Labuhan Maringgai that cutting mangrove, there were fishermen activity in TNWK, transmigration program in Labuhan Maringgai, and land clearing into ponds in Pasir Sakti, the local government issued a regulation: Peraturan Daerah Kabupaten Lampung Timur Nomor: 03 Tahun 2002 (Rehabilitation of Coastal, Coastal and Marine in East Lampung regency), and many mangrove conservating program organized by Lampung Mangrove Center (LMC) in Labuhan Maringgai and mangrove conservator group (Mutiara Hijau I) in Pasir Sakti. Keywords: mangrove, land cover change, GIS, coast of East Lampung Regency